Mechanical conductance tunability of a porphyrin–cyclophane single-molecule junction. Issue 3 (6th January 2022) - Schosser, Werner M.; Hsu, Chunwei; Zwick, Patrick; Beltako, Katawoura; Dulić, Diana; Mayor, Marcel; van der Zant, Herre S. J.; Pauly, Fabian
Abstract : Porphyrin cyclophanes offer a large mechanical tunability of intramolecular π-orbital overlap. This leads to order of magnitude variations in conductance due to two destructive quantum interference dips as evidenced theoretically and experimentally. Abstract : The possibility to study quantum interference phenomena at ambient conditions is an appealing feature of molecular electronics. By connecting two porphyrins in a cofacial cyclophane, we create an attractive platform for mechanically controlling electric transport through the intramolecular extent of π-orbital overlap of the porphyrins facing each other and through the angle of xanthene bridges with regard to the porphyrin planes. We analyze theoretically the evolution of molecular configurations in the pulling process and the corresponding changes in electric conduction by combining density functional theory (DFT) with Landauer scattering theory of phase-coherent elastic transport. Predicted conductances during the stretching process show order of magnitude variations caused by two robust destructive quantum interference features that span through the whole electronic gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO). Mechanically-controlled break junction (MCBJ) experiments at room temperature verify the mechanosensitive response of the molecular junctions. During the continuous stretching of the molecule, they show conductance variations of up to 1.5 orders of magnitude over single breaking events. Uncommon triple- and quadruple-frequency responses are observed in periodic electrode modulation experiments with amplitudes of up to 10 Å. This further confirms the theoretically predicted double transmission dips caused by the spatial and energetic rearrangement of molecular orbitals, with contributions from both through-space and through-bond transport.